Creating new opportunities for tourism development through cross-border collaboration: Shedding light on overlooked destinations - Maria Carmen Pardo; Sofia Almeida; Ana Cláudia Campos (Tourism and Hospitality Management, 2024)
Purpose – The aim of this investigation is to explore opportunities for advancing cross-border tourism in the Iberian Peninsula. Methodology/Design/Approach – In this study, focus groups and in-depth interviews were conducted to both public and private stakeholders in the cross-border regions. Findings – Findings indicate that the cross-border areas in Portugal and Spain are perceived by stakeholders from both countries as familiar territories and also that there are signs of transnational cooperation. This indicates there is significant potential for the advancement of cross-border tourism in the Iberian Peninsula. Nonetheless, the study concludes that more initiatives are required, beginning with the creation of an adequate organization to build the cross-border destination. Originality of the research – The research delivers managerial insights to assist public and private actors in developing this cross-border destination, such as the need to curtail contextual expenses or accentuate the public sector’s role in stimulating private sector’s involvement in the process.